Avaliação clínica retrospectiva de próteses sobre implante com pilares UCLA calcináveis - Silva, Thamires Diuquele da (2018)
Clinical studies regarding prosthetic and periodontal conditions of rehabilitations with implant-supported fixed partial prostheses with UCLA abutment are needed. The aim of this study was to evaluate splinted posterior fixed partial prostheses on external hexagon (EH) implants, with UCLA totally castable abutments, after at least 4 years in function. The maximum bite force (MBF), patient satisfaction, the oral health impact in quality of life (OHIP-14) and marginal bone loss by radiography were evaluated. The clinical exam was performed by checking the prosthesis conditions, occlusion, periimplant tissues and implant conditions. Statistical analysis was made with Student t-test, Spearman nonparametric correlation and Kaplan–Meier estimator (α=.05). Thirty-five prostheses were evaluated in 23 patients (11 men and 12 women, 41 to 90 years) with a total of 85 EH implants and follow-up of 4 to 10 years. Men presented significantly higher MBF values than women (P=.008). The data of OHIP-14 ranged from 0 to 6.64 points. Considering marginal bone loss (mean=2.3mm) and years of prosthesis in function, no correlation was observed (r=0.19, P=.27). During the clinical examination, 8 loosened and 2 fractured screws were found. The contact point was absent in 22 crowns. The plaque was present in 69 crowns. Two implants presented loss of osseointegration and were replaced before prosthesis placement. A positive correlation was found between width of keratinized mucosa and mucositis (r=0.313, P=.003). The estimated Kaplan-Meier survival rate for partial prosthesis showed 98.8% prosthesis survival and 100% implant survival. Splinted posterior prostheses with UCLA totally castable abutments screwed on EH implants are a suitable treatment option when well indicated, with prevention of parafunctional habits, besides considering the maintenance of good oral hygiene and a favorable occlusion over the years